Calculation of Last Current Loop Parameters and TRV Parameters in T100a Breaking Test of High Voltage Circuit-breakers - HE Ninghui; WAN Hua; XUE Fei; WU Hui; ZHANG Pei; MA Kui (Journal of Harbin University of Science and Technology)
Asymmetric short-circuit fault breaking test T100a is an important test item of High-voltage AC Circuit-breakers. In non-effectively earthed neutral system the first pole to clear factor is 1.5 and the transient recovery voltage (TRV) has two or four parameters. By establishing the expression of short-circuit current and voltage in T100a breaking test, the last current loop parameters and TRV parameters are analyzed and calculated in major loop and extended major loop. Finally, the last current loop parameters and TRV parameters are calculated by taking T100a interruption test of rated voltage 40. 5 kV and rated voltage 126 kV Circuit-breakers as examples, which provide an assessment basis for the breaking test of circuit breakers.